How to increase housing affordability: Understanding local deterrents to building multifamily housing - Amrita Kulka; Aradhya Sood; Nicholas Chiumenti (Federal Reserve Bank of Boston, 2022)
This paper studies how local land-use regulations and community opposition affect the trade-offs to building single-family, multifamily, and affordable housing and how their effects on rents differ from their effects on house prices. Using lot-level zoning regulations and a boundary discontinuity design at regulation boundaries in Greater Boston, we obtain causal estimates for the effects of zoning regulations on the supply of different types of housing, single-family-house prices, multifamily rents, and households' willingness to pay for higher density. We find that relaxing density restrictions (minimum lot size and maximum number of dwelling units)-either alone or in combination with relaxing maximum-height restrictions or allowing multifamily housing-is the most fruitful policy reform for increasing the housing supply and reducing multifamily rents and single-family-house prices. However, adopting multifamily zoning or relaxing height regulations alone has little effect on the number of units built or on rents. Moreover, in each land-use relaxation scenario where rents fall, house prices also fall, complicating the political economy of land-use reform. We also find that mature suburbs that are closer to a city center and have a representative town meeting structure of local governance are the most restrictive with respect to adding multi-unit housing. Furthermore, inclusionary zoning policies such as Massachusetts's Chapter 40B rarely substitute for relaxing zoning regulations, particularly restrictions on building multifamily housing.
Keywords: R21; R31; R58; H77; H11; 330; multifamily zoning; height restrictions; density; house prices; rents